Assessing accessibility in environmental education with an emphasis on the d/Deaf and hard of hearing community - Wolken, Brady Kyle (My University, 2025)
Accessibility is a topic that has been explored more often in the last decade. Still, levels of accessibility and how to increase accessibility have been studied less within the scope of environmental education (EE). Accessibility can be defined differently when considering EE and nature-based experiences. The first is in the sense that it can be accessed (location, safety, necessary amenities, etc.), and the other defining factor focuses on whether the activity is barrier-free for participants (physical disabilities, mental disabilities, monetarily, socially, etc.). This study will focus on two projects that assess accessibility within the field of EE. The first project utilizes data from a mixed-method EE provider survey that the Plains Environmental Education Partnership completed in 2023 (n=301). The selected data from this survey include aspects of accessibility, including justice, equity, diversity, and inclusion (JEDI) initiatives, black Indigenous or a person of color (BIPOC) staff, disability accommodations, and diverse audience participation. General results from this project show that steps are being taken towards a more accessible EE. However, identified gaps within EE highlighted support for the need for initiatives to make EE genuinely accessible for all. The second project assesses if EE is accessible to individuals who are d/Deaf or hard of hearing (DHH). This was done using a qualitative online survey with aspects that shape accessibility in EE. Aspects inquired about include perceived barriers and belongingness within EE experiences. From this study, we receive insight into the Deaf or HH view of the world of EE. From our participants (n=1), they concluded that there are multiple barriers, and they have a low sense of belongingness. Due to these barriers and a low sense of belongingness, the respondent is less likely to interact with EE programs and activities. Overall, this collective thesis aims to expand the current understanding of accessibility within EE and how this information can be applied to future ventures to ensure the future of EE is more accessible.
Keywords: Accessability; Deaf or hard of hearing; JEDI; Environmental education